Early Infantile Epileptic Encephalopathy in asparagine-linked glycosylation thirteen (ALG13) gene defect and dramatic response with Ketogenic diet - Prem Chand; Sulaiman, Asna; Angez , Meher; Kirmani, Salman (Journal of the Pakistan Medical Association, 2023)
Asparagine-linked glycosylation thirteen (ALG13) gene-related congenital disorders of glycosylation (CDGs) include early onset epileptic encephalopathy (EIEE), developmental delays (DD) with intellectual disability (ID), speech and visual abnormalities, and haematologic and endocrine dysfunctions. Worldwide there is a scarcity of available data on this. To add to this scarce data, we report the case of a young girl with this rare genetic mutation who showed remarkable improvement in her seizures by addition of ketogenic diet (KD) to her management regimen. With an already high rate of consanguineous marriages, metabolic and genetic errors are widely prevalent; hence, to bridge the huge gap in the understanding of such diseases, further research and trials are needed to be carried out to improve identification of the disease along with outcomes. Keywords: AGLT13 mutation, epileptic encephalopathy and ketogenic diet.